Development of sero-diagnostic and molecular tools for the control of important tick-borne pathogens of cattle in Africa - Morzaria, S.P.; Katende, J.; Musoke, A.J.; Nene, Vishvanath M.; Skilton, Robert A.; Bishop, Richard P. (1999)
Tick-borne diseases (TBDs) are a major economic constraint to livestock production in sub-Saharan Africa. ILRI is focussing on developing a range of products, such as vaccines, diagnostics and decision support services to underpin improved control programmes against these diseases. We have developed three highly sensitive and specific enzyme linked immuno-assays (ELISAs), which allow precise diagnosis of Theileria parva, Babesia bigemina and Anaplasma marginale. These tests have been standardised and validated using defined experimental and field infection sera. Parasite specific recombinant antigens and monoclonal antibodies against bovine immunoglobulins as secondary antibodies have played an important role in enhancing the sensitivity and specificity of the assays. They have been further evaluated in on-farm longitudinal sero-epidemiological studies to define infection dynamics and disease risks in various farming systems in Kenya and Uganda. In addition, DNA-based tests for differentiation of Theileria species and characterisation of Theileria parva stocks have been developed. These tests have been derived through physical mapping and sequencing of key elements of the T. parva genome, which include repetitive and telomeric regions, minisatellite sequences, antigen genes and a number of random DNA sequences. These tools are currently being deployed in conjunction with field immunisation programmes to determine the biological impact of introducing live vaccines of T. parva on population dynamics.